If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 2j = -2 Solving -10 + 2j = -2 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2j = -2 + 10 Combine like terms: -10 + 10 = 0 0 + 2j = -2 + 10 2j = -2 + 10 Combine like terms: -2 + 10 = 8 2j = 8 Divide each side by '2'. j = 4 Simplifying j = 4
| 6x(4+3)= | | X^72/8x^4 | | -5(x-1)=-10x+20 | | B^0/ba^5 | | (9)(10)-(3)(4)= | | 3w+6+4w= | | 5x+6y=67 | | 7x(1/3xN)-4=10 | | 6x-3=14x-19 | | 4(z-3)=5-3z | | (7(1/3y))-4=10 | | (M)(10)=n | | 5x-10(x-2)=x^2 | | 3ab^2-6b= | | 15x=7x-(11-4x) | | 0.75x=24 | | X^72/8x4 | | 2p/3p | | 8.1a+2.3=5.1-3.1 | | 5b-5=7b | | y=-(x+9)2-15 | | 5(x+7)=10x+20 | | C=320+5+3 | | 50=2(2x-5) | | 1898-160= | | 2x-2(x+3)=-6 | | 1898-120= | | 4a+27=9a+8 | | (X+5)(x-5)=90 | | 3/5x-y=52 | | 17=x-2 | | 30b+30m=16b+44m |